1995
DOI: 10.1093/jn/125.suppl_8.2281s
|View full text |Cite
|
Sign up to set email alerts
|

Policy Implications of New Scientific Knowledge

Abstract: Recent research findings have augmented the nutrition variable to a higher category of importance than previously appreciated. Inadequate nutrition can impair cognitive development and is associated with educational failure among impoverished children. This suggests that poor nutrition interferes with the formation of human capital, the cornerstone of a nation's social and economic development. Even temporary food shortages can produce adverse outcomes in developed as well as developing countries. The long-hel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

1996
1996
2010
2010

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(3 citation statements)
references
References 6 publications
0
3
0
Order By: Relevance
“…A study of a 1958 British birth cohort, which defined undernutrition in terms of low weight-forage and sex (the 5th percentile of relative median weight was used as the cutoff point), found that 30% of the children who were underweight at 7 y of age were still underweight at 23 y of age (35), but to our knowledge, no reported studies have examined tracking of underweight in lower-income countries, although there is abundant literature on studies of stunting. Given the high prevalence of undernutrition among children in most developing countries (eg, 17% of our subjects were underweight at baseline) and its serious adverse consequences (35)(36)(37)(38), our findings suggest that, even in a country experiencing remarkable reductions in poverty and improvements in nutrition, it is crucial to prevent early childhood undernutrition or the effects will persist.…”
Section: Discussionmentioning
confidence: 87%
“…A study of a 1958 British birth cohort, which defined undernutrition in terms of low weight-forage and sex (the 5th percentile of relative median weight was used as the cutoff point), found that 30% of the children who were underweight at 7 y of age were still underweight at 23 y of age (35), but to our knowledge, no reported studies have examined tracking of underweight in lower-income countries, although there is abundant literature on studies of stunting. Given the high prevalence of undernutrition among children in most developing countries (eg, 17% of our subjects were underweight at baseline) and its serious adverse consequences (35)(36)(37)(38), our findings suggest that, even in a country experiencing remarkable reductions in poverty and improvements in nutrition, it is crucial to prevent early childhood undernutrition or the effects will persist.…”
Section: Discussionmentioning
confidence: 87%
“…Undernutrition, even moderate and mild forms, has many signi®cant adverse effects. Under-nutrition affects not only children's and adolescents' physical and mental development, but also their emotional stability and behavioral development (Pollitt, 1994;Agarwal et al, 1995;Brown & Sherman, 1995;Gorman, 1995;Grantham-McGregor, 1995;Wachs, 1995). However, there is minimal published research on adolescents' nutritional status in developing countries.…”
Section: Nutrition and Diet Of Chinese Adolescents Y Wang Et Almentioning
confidence: 99%
“…Nutritional insults early in life have a profound and often permanent effect on the subsequent development of the central nervous system. Clinical studies indicate that malnourished children have more learning and behavioral problems than well-nourished children (1)(2)(3). In a cross-sectional study from a pediatric population residing in a governmental institution, there was a trend toward a greater number of epilepsy cases among malnourished children compared with controls (4 ( 5 ) reported a substantial neuronal loss in deeper cortical layers and in the cerebellum and a uniform glial cell loss throughout the cortex of mildly malnourished rats.…”
mentioning
confidence: 96%